Studi Pelaksanaan PROPER Perusahaan dalam Pengelolaan Lingkungan Hidup Periode 2016-2020 di Provinsi Bengkulu - Abdullah Ibrahim Ritonga; Kastilon, Kastilon; Dhendi Novianto Saputra; Reflis, Reflis; Satria Putra Utama (Yayasan Literasi Sains Indonesia, 2024)
One of the government's efforts to monitor and protect the environment is through the Company Performance Rating Assessment Program in Environmental Management (PROPER), which is the Ministry of Environment and Forestry's flagship program to encourage industry compliance with environmental regulations. The implementation of PROPER has been regulated in the Minister of Environment and Forestry Regulation Number 1 of 2021 concerning the Company Performance Rating Assessment Program in Environmental Management. This research was conducted in Bengkulu City using secondary data through literature study media, journals, the Ministry of Environment and Forestry's Decree regarding Proper for 2016-2020, regulations and legislation regarding environmental protection and management, the LHK regulation regarding PROPER. The results of the research conducted show that the implementation of Proper in Bengkulu Province has not shown maximum results during the last 5 (five) year period. Only 1 (one) company received the green title and the rest still received the blue, red and even black titles. The port, palm oil, rubber, coal mining and mineral subsector industries contributed the most to the red title, respectively.